Corticosteroid Therapy in a Case of Severe Cholestasic Hepatitis Associated with Amoxicillin–Clavulanate - Herrero-Herrero, José-Ignacio (Springer-Verlag, 2010)
Amoxicillin–clavulanate is the most common drug involved in drug-induced liver injury and the single most frequently prescribed product leading to hospitalization for drug-induced liver disease in Spain. The liver damage most frequently associated with amoxicillin–clavulanate is cholestasic type. The latency period between first intake and onset of symptoms is 3–4 weeks on average. A 76-year-old man developed fever, pruritus, and jaundice 3 weeks after having completed treatment with amoxicillin–clavulanate. Liver function tests showed cholestasic hepatitis (up to 50.75 mg/dL of total serum bilirubin level). The ultrasound-guided liver biopsy revealed severe canalicular cholestasis and portal and lobular eosinophilic infiltrates. Prednisone and ursodeoxycholic acid therapy were then prescribed. The patient became symptom-free with normal liver function tests. Amoxicillin–clavulanate can cause hepatocellular, cholestasic, or mixed liver injury. The presence of eosinophilic infiltrates in the liver biopsy and the clinical signs of hypersensitivity in some of the cholestasic cases suggest a pathophysiological immunoallergic mechanism. For this reason, corticosteroid treatment should be considered for patients with severe cholestasic liver injury.